Challenges and Opportunities for Women’s Political Leadership in Tigray Region Post-1995 - Girmay, Daniel; Zeray, Haregot; Kidanu, Komais (Journal of Humanities and Social Sciences (JHASS), 2025)
In Ethiopia, women’s leadership was not constitutionally recognized under the past two regimes, and gender issues were highly marginalized. However, following the 1995 Constitution, various gender-related provisions were drafted and implemented, including the introduction of quota systems and affirmative action. Additionally, different pressure groups and advocacy organizations, such as the Ethiopian Women’s Association, Tigray Women’s League, Tigray Women’s Association, and women’s affairs offices, were established to promote women’s rights and participation. This study was conducted to examine the challenges and opportunities of women’s political leadership in the Tigray Regional State after 1995, with a focus on Tigray regional bureaus. The objectives were to assess the challenges hindering women’s participation in political leadership, investigate the government’s role in empowering women and enforcing policies in practice, examine the role of women’s organizations and associations in promoting equal political involvement, and identify opportunities to enhance women’s leadership participation. To address these objectives, a qualitative research method was employed to capture the in-depth views and experiences of participants. Data were collected from both primary and secondary sources. Primary data were obtained through in-depth interviews, key informant interviews, and focus group discussions, while secondary data were drawn from regional policies and strategies. The findings reveal that, although some progress has been made, women remain underrepresented in political leadership and decision-making positions, particularly at higher levels. Their limited participation results from personal, psychological, socioeconomic, cultural, political, and structural barriers. Moreover, despite clear policy directions, gaps persist in implementation. The study recommends strengthened efforts by women’s organizations, government bodies, the regional ruling party, and other stakeholders to enhance women’s political leadership participation.